2020
DOI: 10.1111/jfpp.14794
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antibacterial activity of essential oil vapor released from a paper egg tray in combination with UV‐C radiation against pathogenic bacteria on chicken eggs

Abstract: Paper egg trays are widely used to transport eggs from farms to consumers. Unfortunately, pathogenic bacteria occur on egg trays, which are then transferred to eggs (Utrarachkij et al., 2012). Salmonella enterica serovar Typhimurium, Escherichia coli, and Staphylococcus aureus are the most common types of pathogenic bacteria on eggs. Salmonella bacteria can survive on the outer surface of eggshell, potentially penetrating through the inner egg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…However, in the present study, the egg score was similar or higher in comparison to the control treatments, suggesting that the treatments did not affect the odor and flavor attributes measured by consumers. This result is comparable to that of Phothisuwan et al (2020), who found that the overall acceptability of eggs kept on the treatment tray (40 μg g −1 of clove oil) was not significantly different from the control, with opinions ranging from like slightly to like moderately. Consumers preferred eggs that were safe and have a satisfactory sensory score.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…However, in the present study, the egg score was similar or higher in comparison to the control treatments, suggesting that the treatments did not affect the odor and flavor attributes measured by consumers. This result is comparable to that of Phothisuwan et al (2020), who found that the overall acceptability of eggs kept on the treatment tray (40 μg g −1 of clove oil) was not significantly different from the control, with opinions ranging from like slightly to like moderately. Consumers preferred eggs that were safe and have a satisfactory sensory score.…”
Section: Resultssupporting
confidence: 87%
“…Eggs are an exceptional source of protein, nutrients, vitamins, minerals, bioactive compounds, immune factors, complex structural lipids required for lipid homeostasis, and rich in all kinds of essential amino acids (Wood et al, 2021; Zhou, Liu, Wang, Liu, & Wu, 2021). Unfortunately, pathogenic bacteria, such as Escherichia coli , Salmonella enterica serovar Typhimurium, and Staphylococcus aureus , remain potential threats to human health via contaminated eggs (Phothisuwan, Preechatiwong, & Matan, 2020). Eggs from different poultry systems throughout the year serve as a possible source of these organisms (Tomar, Akarca, Istek, & Ataseven, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of food safety and packaging, this result is in agreement with other reports that EO could be applied in biomaterial-based food packaging (Matan et al 2011;Suhem et al 2019;Songsamoe and Matan 2020). Phothisuwan et al (2020) also demonstrated that paper egg tray containing 10 to 80 µg g −1 clove oil could inhibit E. coli, Salmonella enterica serovar Typhimurium, and S. aureus on chicken eggs for 30 days. This study showed the ability of coconut, rubberwood, and palm to adsorb and release EO and inhibit the bacteria kept inside the fiber sachets in the closed box.…”
Section: The Effect Of Essential Oil Emulsion Containing In Natural Cellulosic Materials Against Foodborne Pathogensmentioning
confidence: 90%
“…The CM can be made from a plant product, e.g., bamboo fibre or a water plant, which replaces synthetic materials, e.g., foam or plastic, in an effective way to protect the banana. These plant fibres have beneficial properties, e.g., they absorb energy, are lightweight, and have excellent physical properties (Phothisuwan et al 2020). In addition, based on their structural characteristics, e.g., intelligent, functionally graded material (Tan et al 2011), they have a low density and low cost due to their high growth rate and high degree of strength (Hao et al 2018).…”
Section: Introductionmentioning
confidence: 99%